Analisis Perilaku Manajemen Keuangan di Kalangan Mahasiswa - Dyah Kusumawati; Faiq Fuadi (Universitas 17 Agustus 1945 Semarang, 2024)
The purpose of this study was to determine how much students' attitudes toward financial management were influenced by their social surroundings, financial experience, and financial literacy. This kind of study uses a quantitative, explanatory methodology. The population is students of the Faculty of Economics and Social Sciences Sultan Fatah University Demak as many as 110 people. Because the entire population is used, the sampling method uses saturated samples. Information was gathered using an online survey and using multiple linear regression analysis techniques. Respondents' answers were measured using a Likert scale with SPSS version 25 tools. According to the study's findings, the dependent variable is significantly impacted by each independent component taken combined. Taken alone, financial management literacy is not influenced by the social environment, while financial management literacy is significantly influenced by financial experience and financial literacy.